To assess mental health literacy among MBBS students about Psychiatric issues at Patna Medical College - Singh, Vivek Pratap; Satyadarshee, Kumar; Singh, Narendra Pratap (Asian Journal of Medical Sciences, 2021)
Background: Mental health is a big problem throughout the world, and India is not far behind. When we look at progress in the field of mental health, it appears to be sluggish. Despite the fact that a newly created mental health literacy (MHL) scale revealed substantial score disparities between the general public and mental health professionals, there is currently no published scale to measure MHL among healthcare students. Aims and Objectives: The major part was comparing the knowledge, attitude and perception of 1st year medical students with final year medical students regarding psychiatric disorders and measuring there response on Likert scale. Materials and Methods: The participants were recruited from 1st year to final year undergraduate students, during the period April 2019 to January 2020 in Patna Medical College and Hospital, Patna. The sample consisted of 100 students (50 from 1st year MBBS Students and 50 from final year MBBS (Students) Non-random, non-stratified, and purposive sampling was done for the purpose of the study. Results: Among the groups, majority of the of the final year students (64%) agreed that the best described condition of the patient was Generalized Anxiety Disorder, but only 26% of the 1st years students agreed that the best described condition of the patient was Generalized Anxiety Disorder. There was significant difference between 1st years and final year students about the knowledge of the described condition with P<0.001. Conclusion: Result showed that the final year students had more knowledge about the cases with regard to correct diagnosis, usefulness of various treatments and interventions and best the source of help. The 1st and final year student had no differences in the attitude and perception regarding various cases given in the vignettes. Stigma based attitude was almost equally common among both 1st year and final year students.